Cryopreservation and transplantation of common carp spermatogonia - Franěk, Roman; Marinović, Zoran; Lujić, Jelena; Urbányi, Béla; Fučíková, Michaela; Kašpar, Vojtěch; Pšenička, Martin; Horváth, Ákos (PloS one, 2019)
Common carp (Cyprinus carpio) is one of the most cultured fish species over the world with many different breeds and plenty of published protocols for sperm cryopreservation. However, data regarding preservation of gonadal tissue and surrogate production is still missing. A protocol for freezing common carp spermatogonia was developed through varying different factors along a set of serial subsequent experiments. Among the six cryoprotectants tested, the best survival was achieved with dimethyl sulfoxide (Me2SO). In the next experiment, a wide range of cooling rates (0.5-10°C/min) and different concentrations of Me2SO were tested resulting in the highest survival achieved using 2 M Me2SO and cooling rate of -1°C/min. When testing different tissue sizes and incubation times in the cryomedia, the highest viability was observed when incubating 100 mg tissue fragments for 30 min. Finally, sugar supplementation did not yield significant differences. When testing different equilibration (ES) and vitrification solutions (VS) used for needle-immersed vitrification, no significant differences were observed between the tested groups. Additionally, varied exposure time to VS did not improve the vitrification outcome where the viability was 4-fold lower than that of freezing. The functionality of cryopreserved cells was tested by interspecific transplantation into sterilized goldfish recipients. The exogenous origin of the germ cells in gonads of goldfish recipient was confirmed by molecular markers and incorporation rate was over 40% at 3 months post-transplantation. Results of this study can serve for long-term preservation of germplasm in carp which can be recovered in a surrogate recipient.
Keywords: časové faktory; Carps; Spermatogonia; spermatogonie; dimethylsulfoxid; Time Factors; Male; kapři; Animals; kryoprezervace; Dimethyl Sulfoxide; mužské pohlaví; zvířata; Cryopreservation